Assessment of meat microbial contamination inAlkadro slaughterhouse, Khartoum State,Sudan (Journal of Veterinary Medicine and Animal Production, 2022)
This study was conducted to evaluate the bacterial contamination of meat in Alkadro slaughterhouse. One hundred and twenty swab samples were taken from different stages in carcasses line, as well as inspection of knives, hocks, tables, worker hands and air. The samples were subjected to viable bacterial count and the meat was tested for the pH values. Causes of condemnation of organs were also recorded. The percentages of causes of condemnations from the total number of condemned organs: in beef, were fasciola spp in livers were (46.03%), aspiration pneumonia in lunges (3%) and abscess in head (7.5%). In mutton, abscess in livers were (64.4%), hydatid cysts in livers (2.9%), pneumonia in (9.7%), Hearts due to the adhesions of pericardium (2.9%) and abscess (0.4%). For viable bacterial count, air samples showed a maximum level in evisceration site (80.8 CFU/plate), inspection site (63.25 CFU/plate), skinning site (51.80 CFU/plate) and in washing site (40.40 CFU/plate). Tables, workers’ hands, knives, hooks and carcasses, showed that the maximum level counts in hooks (4.8×103 CFU/cm2) and the minimum level count were in hands (2.7×103CFU/cm2). Carcasses after skinning showed the minimum level count 1.34 ×102 CFU/cm2. pH of meat ranged between (5.7 – 6.4). This study revealed that there is high level of contamination in slaughterhouse. Hence to reduce of meat contamination should be start with the implementation of good hygienic practices and good manufacturing practices and implementing HACCP system. In addition to health education and training are needed to raise the awareness for meat handlers in the slaughterhouses.